(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate pelvic floor functionality and sexual function in pregnant women. The study was characterized as a descriptive and transversal research. The population consisted of 19 pregnant women, living in Parnaíba/PI. The women’s assessment instruments were the evaluation and identification form that contained sociodemographic data, clinical history, obstetric and urogynecological data; the NEW PERFECT scheme was used to assess the functionality of the pelvic floor muscles and the Female Sexual Function Index (FSFI) to assess sexual function. Mean age was 25.95 (± 3.54) years, mean pelvic floor muscle strength was 2.47 (± 1.28); resistance was 4.31 (± 2.99) seconds; the number of repetitions of the contractions maintained was 2.63 (± 1.6) times; and rapid contractions were 5.05 (± 2.87) contractions. Sexual function according to the FSFI totaled a score of 25.61. In this study, it was possible to infer important deficiencies and limitations regarding strength, coordination, control and activation of the pelvic floor muscles. As in the sexual function domain, the FSFI result indicates possible dysfunctions with an emphasis on the hypoactivity of sexual desire.